2016
DOI: 10.1186/s12931-016-0467-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-neuronal cholinergic system contributes to corticosteroid resistance in chronic obstructive pulmonary disease patients

Abstract: BackgroundInhaled corticosteroid (ICS) with long-acting beta-2 agonists is a well-documented combination therapy for chronic obstructive pulmonary disease (COPD) based on its additive anti-inflammatory properties. By contrast, the recommendation of ICS in combination with long-acting muscarinic antagonist (LAMA) is not evidence-based. In this study, neutrophils obtained from COPD patients were used to compare the anti-inflammatory effects of aclidinium bromide (a long-acting muscarinic antagonist) with cortico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 38 publications
5
29
0
1
Order By: Relevance
“…Peripheral blood neutrophils were isolated from peripheral venous blood and cultured as previously described [9]. Neutrophils were adjusted to 500×10 3 cells per well in 24-well plates and incubated in RPMI 1640 for 1 h at 37°C, 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral blood neutrophils were isolated from peripheral venous blood and cultured as previously described [9]. Neutrophils were adjusted to 500×10 3 cells per well in 24-well plates and incubated in RPMI 1640 for 1 h at 37°C, 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Although evidence for drug combinations comes from clinical trials, scientific rationale for drug combinations can be explained by molecular interactions as previously outlined [58]. Recent evidence provided by our group indicates that LAMA can improve corticosteroid insensitivity in neutrophils from COPD patients inhibiting PI3Kδ and enhancing glucocorticoid response element transcription factor (GRE) with the consequent increased expression of corticosteroid anti-inflammatory related genes [9]. Although not studied in detail, these results indicate potential anti-inflammatory synergism between triple therapy based in LABA + LAMA + ICS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is some evidence that aclidinium bromide could modulate the non-neuronal cholinergic system, a recently identified regulatory pathway in pulmonary inflammation and remodeling [28]. Dysfunction of the non-neuronal cholinergic system seems to be involved in the pathophysiology of COPD and to some extent in resistance to corticosteroid therapy; in fact, non-neuronal cholinergic system is over-expressed in corticosteroid-insensitive neutrophils from COPD patients, as evidenced by increases in the expression of muscarinic receptors (M2, M4 and M5), vesicular acetylcholine transporter (VAChT) and choline acetyltransferase (ChAT).…”
Section: Main Textmentioning
confidence: 99%
“…Mitogen-activated Protein Kinase Phosphatase 1 (MKP1), Cysteine-RIch Secretory Protein LCCL Domain-containing 2 (CRISPLD2) and (GILZ) [28]. Among aclidinium bromide therapeutic properties, it seems to be interesting as well its favourable effect on hyperinflation and airflow limitation, that plays a very important pathophysiological role in inducing dyspnea and reducing quality of life (QoL) in COPD patients; in this regard, it has been recently demonstrated that aclidinium promotes a rapid and relevant desufflation and improves lung ventilation inhomogeneity, even in severe/very severe COPD patients [29].…”
Section: Main Textmentioning
confidence: 99%
“…Airway remodeling is associated with the process of airway inflammation, which predominately occurs in the lungs [ 3 ]. Since the pathogenesis of COPD is not yet fully understood [ 4 ], such research is typically focused on four aspects which include (1) lung inflammation, (2) the imbalance of lung protease and anti-proteases, (3) oxidation and antioxidation imbalances, and (4) autonomic nervous system dysfunction [ 5 ], such as abnormal cholinergic receptor distribution ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%